Concept of Communication Ethics for Content Creators in Making Videos on the Mata Pena Youtube Channel - Firman Ashari; Ahmad Zurfikar Ali (al-Afkar, Journal For Islamic Studies, 2024)
The purpose of communication ethics is to convey messages and disseminate to the audience, but in delivering these messages there are things that must be considered both in terms of making the video and the conception of content creators in making the video, before publication, both the conception of themes, speech, or actions which must all be adjusted to the ethics in society. The type of research used by researchers is descriptive qualitative research with a case study approach. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of the study can be concluded that the concepts used by content creators in making videos on the Mata Pena youtube channel include, choosing good words or not when they want to be used, adjusting to the circumstances (Life), writing scripts written one by one according to dialogue, rhymes in the script used to beautify sentences, which are included in normative ethics which are divided into social ethics and individuals who are more dominant in social ethics,  As for its application, content creators apply direct and indirect communication, directly in writing or not and indirectly in the sense that it can be through facial expressions, clothes, actions and so on. Thus, the concept of communication ethics by content creators on the Mata Pena youtube channel is divided into individual ethics and social ethics.